Computational fluid dynamics analysis for predicting microaneurysm formation in parent arteries of unruptured cerebral aneurysms: implications for neck clipping safety - Sasaki, Kento; Nakahara, Ichiro; Kihara, Kotaro; Tanaka, Shiho; Tanaka, Riki; Hasebe, Akiko; Tanabe, Jun; Haraguchi, Kenichi; Yamada, Yasuhiro; Komatsu, Fuminari; Okubo, Mai; Katayama, Tomoka; et al. (Frontiers in Neurology, 2025)
BackgroundAneurysmal subarachnoid hemorrhage caused by cerebral aneurysm rupture has a poor prognosis, with mortality exceeding 30% despite treatment advancements. Surgical neck clipping remains the standard for preventing rupture, but intraoperative rupture rates vary significantly (3–50%) and are influenced by vascular complexity and technical challenges. Thinning of the vascular wall near the aneurysm neck, particularly with microaneurysm formation, has emerged as a significant risk factor, yet these changes often go undetected in preoperative imaging.ObjectiveThis study aimed to evaluate the utility of computational fluid dynamics (CFD) analysis for predicting microaneurysm formation in the parent artery adjacent to unruptured cerebral aneurysms, using the parent artery radiation sign (PARS) as a predictive marker.MethodsWe conducted a single-center, retrospective observational study of 89 patients with unruptured middle cerebral artery (MCA) aneurysms treated with neck clipping from May 2020 to April 2022. Based on preoperative three-dimensional computed tomography angiography (3D-CTA), CFD analysis identified PARS through specific hemodynamic indicators. Intraoperative findings were analyzed and compared between PARS-positive and PARS-negative groups. The sensitivity and specificity of PARS for predicting microaneurysm formation were investigated.ResultsOf the 87 aneurysms analyzed, 25 (28.7%) were PARS-positive, and 62 (71.3%) were PARS-negative. Microaneurysms were identified intraoperatively in nine cases, eight of which were in the PARS-positive group. The sensitivity and specificity of PARS for detecting microaneurysms were 89 and 78%, respectively. The positive likelihood ratio was 4.1, while the negative likelihood ratio was 0.142.ConclusionCFD analysis using PARS offers a reliable method for predicting microaneurysm formation in the parent artery, potentially guiding surgical planning and reducing intraoperative rupture risk. While promising, these findings are limited by the retrospective, single-center design, highlighting the need for further research in larger, multicenter cohorts. Incorporating CFD analysis into preoperative assessment could significantly enhance the safety and outcomes of neck clipping procedures for unruptured cerebral aneurysms.